Isolation And Identification Of Biosurfactant Producing Bacteria From The Coastal Area Of Mengkapan Village, Sungai Apit Distict, Siak Regency, Province Of Riau - Apriani Adha Nasution; M. Hasbi M. Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The activities of petroleum drilling, ferry ports and leakages of underwater pipeline caused oil pollution in the coastal area of the Mengkapan Village. The presence of oil pollution may trigger gene mutation in specific bacteria and it may produce biosurfactants for degrading the oil. A study aims to investigate the biosurfactantproducing bacteria in the coastal of Mengkapan village was conducted from March to May 2018. There were 2 stations, in the petroleum drilling area (St1) and in the TanjungButon port (St2). Results shown that the highest bacterial density was inthe St2. Morphological and biochemical characeristics shown that there were 2 bacteria species, namely Bacillus sp and Pseudomonas sp present. Emulsification Index of the Bacillus sp was43% and that of the Pseudomonasspwas 54%, indicating that those bacteria were potencial for producing biosurfactant. Keywords : Microorganisms, Biodegradationt, Oil, Emulsification